IMPLEMENTASI SOLAR TRACKER PADA PLTS OFF GRID UNTUK SISTEM PENDETEKSI BANJIR - Faturrachman, Luthfi; Rozak, Ojak Abdul; Multi, Abdul; Samiaji, Ghani (LPPM Poltek ST Paul, 2024)
Solar energy is an inexhaustible renewable energy resource. This can also be used as energy that can be converted into electricity. Due to the importance of using electrical energy, electricity network management companies in Indonesia continue to experience price per kwh increases in proportion to the increasing amount of electrical energy consumption. Therefore, alternative energy is needed which functions as an energy generator. On this basis, the author tries to design a power plant using solar power. This test uses two methods, before using the solar tracker and after using the solar tracker. The results of calculating the average power value for ten days of testing before using the solar tracker were 44.3 watts, and the results of calculating the average power value for ten days of testing after using the solar tracker were 53.1 watts. The results of comparing the average power value before and after the implementation of the solar tracker showed an increase in power value of 8.8 watts. The off-grid solar system is able to meet the needs of the system load. The implementation of the use of solar trackers on solar panels is able to increase the value of the generated power.